Anti-depressant effects of acupuncture: The insights from NLRP3 mediated pyroptosis and inflammation. (10th August 2022) - Chen, Yiping; Hao, Chongyao; Chen, Wenjie; Cheng, Wenjing; Li, Peng; Shen, Junliang; Tong, Tao; Yan, Simin; Huang, Shuqiong; He, Tianwei; Huang, Zhiyong; Meng, Xianjun
Highlights: Acupuncture alleviates CUMS-induced depression-like behavior in rats. Anti-depressant effects of acupuncture may manifest as attenuating NLRP3 mediated pyroptosis and inflammation in hippocampus of CUMS rats. Acupuncture regulates glial and neuronal loss in hippocampus, which was partly responsible for the neuroprotective effects of acupuncture. Abstract: The NLRP3-mediated pyroptosis, which could affect inflammation response, plays a key role in the development of depression. Acupuncture has been shown to be an effective treatment for depression. In this study, we aimed to determine whether acupuncture could confer antidepressant activity via decreasing NLRP3-mediated pyroptosis by reducing inflammation. Here, depression model of rats was induced by chronic unpredictable mild stress (CUMS) for 4 weeks. Acupuncture group was subjected to acupuncture at the Shangxing (GV23) and Fengfu (GV16) acupoints for 20 min every other day (a total of 14 times). Fluoxetine group was administered with fluoxetine (2.1 mg/kg with the concentration of 0.21 mg/mL) by oral gavage (1 mL/100 g) once a day for 28 days. Rats' depression-like phenotypes were reflected with behavioral tests and biological detection methods. Results showed that acupuncture significantly improved the depression-like behavior of CUMS rat, suppressed the expressions of NLRP3, ASC, caspase-1, GSDMD, IL-1β, IL-18, HMGB1, IFN-γ, IL-6 and TNF-α in the serum and hippocampus, restored the %area of microglia, astrocytes and neuronal cells in the hippocampus. These indicate that acupuncture can prevent CUMS-induced depression-like behaviors by reducing NLRP3-mediated pyroptosis and inflammation.